The Influence Of Taste Of Service Quality Of Product Variations On Buying Decision On Gacoan Noodles In Semarang City - Wildan, M. Akmal; Sutrisno; Dharmaputra, M Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
The goal of this study is to identify the factors that impact the purchasing decisions of Gacoan Noodle customers in Semarang City in relation to flavour, service quality, and product variety. This study relies on numerical data. Research participants included residents of Veteran, Peterongan, Tembalang, Ngaliyan, Pamularsih, Majapahit, Banyumanik, Jl Imam Bonjol, and Arteri Soekarno Hatta, who were Mie Gacoan consumers in the Semarang City region. One hundred participants served as samples for this research. This research makes use of SEM-PLS analysis to sift through primary data. This study found that taste significantly influences purchasing decisions in a good way. In terms of impact on purchase decisions, service quality is insignificant. The impact of product variation on consumer purchasing behaviour. The Gacoan Noodle should aim to improve the flavour of their noodles, the quality of their customer service, the diversity of their products, and their prices so that they can compete with other spicy noodle joints. We intend to include product presentation, brand image, and other elements that are believed to impact purchasing decisions via pricing in future studies.